Application of Shuffled Frog Leaping Algorithm (SFLA) to long term generation expansion planning / Nurul Ulya Ibrahim - Ibrahim, Nurul Ulya (2016)
This thesis presents a solution to generation expansion planning problem based on Shuffled Frog Leaping Algorithm (SFLA). The proposed SFLA in this study is developed using Matlab programming. This method is tested for 15 existing power plant and five generation candidates within 10 years of planning. The simulation results obtained using the proposed algorithm show that the minimum cost can be obtained for types of candidate.